Three dimensional human body pose estimation - Biason, Janelle J. (2000)
In this paper, estimation of human body pose doing lateral movements in monomial view (single camera) is described. Sensors and special devices are not utilized in this project. The subject stands in front of the camera. The model on the screen imitates whatever movements the subject is doing (provided they are lateral movements only). It is assumed that there is only moving person in perspective and there is minimal light variance. The approach here is to detect motion regions from video frames using double difference image. This stakes three successive bitmap images, gets the pixel difference of the first and the second, and the second and the thrid images and implements an "OR" operation for the motion region detection "AND" operation for the double difference image. Dividing the pixels into groups of 16 are implemented to disparage cost in image processing as well as noise in images. Contour based method is then used in determining the pose of the subject. At the start, a calibration or initial pose for model matching purposes is needed. There are three models used in this project. One model has a hierachy (i.e. torso is the parent or left upper arm and right upper arm), the other one has no hiearchy and lastly, a model which is just a mirror image of the one with hierachy. The latter is used in displaying the estimated human body pose and is can be viewed by the users in four ways: front, back, left side and right side.